Descrição de pero, sino, sin embargo, na tradição gramatical e na semântica argumentativa, e implicações pedagógicas - Moraes, Gisele Benck de (2005)
One of the difficulties the Spanish teachers and students face is the teaching and learning of the adequate use of pero, sino and sin embargo, not only in the reception but also in the text production. Reflecting about this fact, the following hypotheses were elaborated: this difficulty has its origin in the description of these morphemes, which are presented in grammar books, dictionaries and didactical books, used in the teaching of the Spanish language to foreigners, and the description done by the Theory of Argumentation within Language (TAL), by Ducrot and Anscombre and by the Theory of the Semantic Blocks (TSB), by Marion Carel, could help in the solution of this difficulty. In this way, after having verified the traditional description of these morphemes and the argumentative- semantic description, a first test (Test 1), containing two parts A and B, composed by texts from the book El libro de los abrazos by Eduardo Galeano, was applied to the students who were finishing Letras Spanish Language Competence. The part A, filling the gaps, had the purpose of verifying if the students knew when to use each one of the morphemes. The part B required the justification, even in texts, of the permanence or replacement of pero by sin embargo. Having carried out this first test, which proved the students difficulty mentioned before, some classes were taught with the objective of distinguishing these morphemes in the light of TAL and TBS. After that, the same test was applied, called Test 2 then. Through the comparison of the results of the two tests, it is permitted to affirm that the instructional description, which is the open one of TAL and TSB is more adequate to teaching than the traditional description, the one which tries to describe all possible contexts, a task which seems impossible